Apocalyptic television - Leslie Harris (Communicare)
Since the beginning of the decade the world has shrunk through the growth of global mass communication and Information highways. Greater access to Information makes the consumer more susceptible to propaganda, disguised by Information providers as objective information. A prime example of this manipulation occurred during the Gulf War of 1991 . Through effective use of propaganda techniques the Bush administration created a situation torclng the western world to Involve itself in a domestic dispute In the Middle East Prime benenclarles were the Bush Administration, and George Bush himself, who at the time was seeking re-election as president of the United States. Analysis of media coverage of the war, particularly the coverage on CNN, will show how the mass media assisted the administration In creating and sustaining the climate for war. Two of the world's current "hot spots" will be considered briefly against the framework of the Gulf War- the military intervention in Haiti for Its .Similarities and change In South Afnea for the perspective it provides on television coverage of world events.